Heavy Metal Pollutants in Snow and Ice from Roosevelt Island, Antarctica - Andrea Tuohy (8510613) (2015)
Global industrialization has led to emissions of heavy metal pollutants that are transported to the most remote areas of the planet. Elevated concentrations of heavy metals are ecological toxins in soils, water, and air. Monitoring has only been implemented during the last few decades with anthropogenic emissions superimposed over natural sources. Furthermore, most monitoring programs generally target local sources of emissions near cities rather than large-scale impacts. Thus quantifying safe limits and controlling industrial emissions is complicated by a lack of knowledge about natural sources and variability on regional, hemispheric, and global scales. New baseline studies are needed to determine i) natural background concentrations of heavy metals, ii) contributions of anthropogenic emissions, and iii) the degree to which atmospheric transport affects background heavy metal concentrations. Due to the remoteness of Antarctica, ice cores can be used as sensitive recorders of background heavy metal atmospheric concentrations over thousands of years. This provides the opportunity to determine natural variability and contributions to the atmosphere on a hemispheric scale, as well as dating the onset of anthropogenic emissions. This thesis presents a 2,300-year time-series record of six heavy metals from a new high-resolution coastal ice core from the Ross Sea region of Antarctica. Roosevelt Island is an ice dome located in the north-eastern Ross Ice Shelf, and a 763m deep ice core was collected over two field seasons as part of the Roosevelt Island Climate Evolution (RICE) project. In addition to 31 other trace elements, concentrations of iron, aluminium, manganese, lead, arsenic, and thallium were measured using inductively coupled plasma mass spectrometry (ICPMS) in the RICE ice core, snow pit, and snow precipitation samples. Sample resolution over the 20th century is extremely high (~1.6 months per sample), with ~four-year resolution extending the record back to 2,300 years ago. We use this record to first determine the representativeness of the RICE ice core to Southern Hemisphere atmospheric concentrations of heavy metals, and find that concentrations in snow precipitation are strongly linked to meridional air mass pathways from the South Pacific. Local deposition characteristics and heavy metal seasonality are also examined in the surface snow. The natural sources and variability of the six heavy metals are explored through the last ~2,000 years, and this provides the context for examining changes over the 20th century. We find that iron, aluminium, and manganese are strongly associated with crustal dust and do not exhibit source changes over the 20th century, though significant increases in concentration may be due to anthropogenically induced increases in atmospheric dust. Even when increased variability due to recent increased efficiency of atmospheric transport is taken into account, the change in source emission strength dominates the concentration increases in these elements recorded in the RICE ice core. Thallium concentrations do not increase over the 20th century, and are likely linked to local volcanism. Both lead and arsenic concentrations increase significantly over the 20th century, with the pattern in lead concentrations closely matching existing Antarctic records. These increases are linked to anthropogenic emissions, with peaks during the 1970s and 1980s up to 400% higher than pre-industrial concentrations – well outside the natural variability. However, the ice core record shows a decreasing trend in concentrations of these elements from the mid-1990s to the present. Arsenic concentrations return to within pre-industrial variability, and the timing of this trend coincides with increasing efforts of policy makers in Southern Hemisphere countries to regulate industrial emissions and to promote public awareness of heavy metal pollutants.